Resource-saving technologies for the basic cultivation of chernozem typical in the northeastern region of the Central Chernozem region - Shabalkin A.V.; Skorochkin Yu.P.; Vorontsov V.A.; Dracheva M.K. (BIO Web of Conferences, 2023)
The research was carried out with the aim of solving the problem of optimizing the system of basic tillage, providing a reduction in energy costs, obtaining high crop productivity and profitability of production in a grain-fallow crop rotation in the conditions of the northeast of the Central Chernozem Region. The work was carried out in 2013-2021, in a stationary field experiment on a typical heavy loamy chernozem with a high supply of mineral nutrients with a humus content in the arable layer of 6.8-7.0%. The scheme of the experiment included the following options for the main tillage systems: traditional mid-depth moldboard, for soybean at 25-27 cm (control); resource-saving: surface (disking by 10-12 cm) for all crops and non-moldboard mid-depth, 25-27 cm for soybeans and 20-22 cm for cereals; combined: moldboard-less plowing (25% plowing for soybeans + 75% non-moldboard semi-deep plowing for cereals) and moldboard-surface (25% plowing for soybeans + 75% surface plowing for cereals). Against the background of treatments for crop rotation, fertilizers and plant protection products were used. It was found that resource-saving non-moldboard and combined tillage for sowing, on average, for crop rotation crops, accumulated more moisture in the arable layer by 12.1-13.8%, by 3.9-7.8% in the meter layer, compared with traditional moldboard cultivation. . Surface tillage reduced the reserve of productive moisture in the arable layer by 4.4%, in the meter layer - by 5.1%. It has been studied that the best nitrogen, phosphorus and potassium regimes are established with traditional dump and combined dump-surface treatments. In the variants with surface and non-moldboard tillage, a decrease in the content of mineral nutrition elements in the arable soil layer is noted. At the same time, there was an increase in the process of differentiation of the arable layer by fertility with a concentration of nutrients in the layer of 0-10 cm and a significant decrease in them in the layer of 20-30 cm. 2.1 times without herbicides, 2.2 times against the background of herbicide treatment, in terms of the number of weeds and 1.4 and 1.5 times in terms of their mass, in comparison with traditional moldboard treatment. The use of herbicides contributed to a decrease in the number of weeds and the mass of the weed component on average for the variants of the experiment by 55.4 and 60.0%, respectively. It was analyzed that the use of surface and non-moldboard tillage systems led to a decrease in the productivity of a hectare of arable land in crop rotation by 0.09 tons of grain units without protection and by 0.11-0.14 tons in combination with plant protection. The combined (dump-surface) system of tillage ensured the productivity of arable land at the level of the traditional dump system at different depths. It has been proved that the highest profitability of production in crop rotation (250.3%) was achieved using a combined (dump-surface) tillage system in combination with the use of complex protection products (seed dressing + pesticides for crop vegetation). Resource-saving processing systems (surface and non-moldboard) worsened economic performance. Income from the use of these tillage systems decreased by 4.8-5.5%, profitability decreased by 1.6-2.7% compared to the traditional mid-depth moldboard tillage system in crop rotation.